(х-19)/32 + 15/32 = 17/32
Домножим обе части уравнения на 32 (чтобы избавиться от знаменателя):
(х-19)/32 · 32/1 + 15/32 · 32/1 = 17/32 · 32/1
(х - 19) + 15 = 17
х - 19 = 17 - 15
х - 19 = 2
х = 2 + 19
х = 21
Проверка: (21 - 19) + 15 = 17
2 + 15 = 17
17 = 17
(х-19)/32 + 15/32 = 17/32
Домножим обе части уравнения на 32 (чтобы избавиться от знаменателя):
(х-19)/32 · 32/1 + 15/32 · 32/1 = 17/32 · 32/1
(х - 19) + 15 = 17
х - 19 = 17 - 15
х - 19 = 2
х = 2 + 19
х = 21
Проверка: (21 - 19) + 15 = 17
2 + 15 = 17
17 = 17